Innovation In Empowering Umkm Through The Trisuaka Mall By The Community And Village Empowerment Agency Village Of Dharmasraya District : Inovasi Pemberdayaan Umkm Melalui Mall Trisuaka Oleh Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Dharmasraya - Rani Handriyani; Adil Mubarak (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Trisuaka Mall is an innovation to empower Micro, Small, and Medium Enterprises (MSMEs) initiated by the Department of Community and Village Empowerment (DPMD) of Dharmasraya Regency. The purpose of this innovation is to improve the family economy through a transparent, responsive, innovative, and sustainable platform. Trisuaka Mall provides two types of services, namely online and offline-based, to promote and sell MSME products. This research aims to examine how the innovation of MSME empowerment through Mall Trisuaka is carried out by DPMD of Dharmasraya Regency. The research method used is descriptive with a qualitative approach. Data was collected through interviews, documentation, and non-participant observation. The results show that Trisuaka Mall has relative advantages and high compatibility with local needs, but faces significant barriers, including technical issues with the website, budget limitations, and lack of understanding of online features. Although mitigation measures such as technical guidance and socialization were implemented, these challenges affected the effectiveness and sustainability of the innovation. In conclusion, with proper handling of existing barriers, Trisuaka Mall has the potential to have a significant positive impact in improving MSME empowerment and the family economy in Dharmasraya Regency. Further efforts are needed to rectify technical issues, improve user understanding, and strengthen budget support to ensure the long-term success of this innovation